Evaluation of vaginal flora and antibiotic prophylaxis in elective hysterectomy in a rural hospital from India - Mahadik, Kalpana V; Pathak, Ashish; Shah, Harshada; Purohit, Manju Raj (International Journal of Infection Control, 2013)
AbstractThe incidence of post-operative morbidities is 11.5% in developing countries and surgical site infections complicates nearly 20% of intra-abdominal procedures. Contamination of operative site with vaginal flora is unavoidable and should be treated prior to hysterectomy. This study was conducted to assess the current status of antibiotic prophylaxis in hysterectomy in a rural setting. The study was conducted at Department of Obstetrics and Gynecology, R.D.Gardi Medical College, Ujjain, India. Patients of abdominal and vaginal hysterectomy for benign gynecological diseases were included. Pre-operative vaginal swab was cultured. Patients with culture negative result received Ampicillin prophylaxis while culture positive patients received antibiotic of sensitivity. Patients were observed for various post-operative morbidities. Total 109 patients with age range of 37- 76 years were analyzed in the study. Pre-operative vaginal swab culture showed non-pathogenic organisms in 67% culture while pathogenic bacteria in 33 % cultures. Culture positive results were more often seen in vaginal hysterectomy than in abdominal hysterectomy (p = .003). Total 25.6% (28/109) patients showed post-operative morbidities such as vaginal discharge, wound infection, urinary tract infection, and fever in decreasing order of frequency. Only 11.1% (4/36) patients infected with pathogenic bacteria and 32.8% (24/73) patients with non-pathogenic bacteria showed morbidities. Morbidities were high in Ampicillin prophylaxis patients than in culture specific prophylaxis (p=.014). This study showed the beneficial effect of pre-operative vaginal swab culture in elective hysterectomy and that a culture sensitive antimicrobial coverage is more effective than Ampicillin in reducing post-operative morbidities.